Modified Extended External Fixator Frame for Leg Elevation in Trauma - Sawant, Venkatesh Rajaram; Gharwade, Chandrakant Rambhau (Indian Journal of Plastic Surgery, 2020)
Lower extremity trauma is very often managed by applying an external fixator to stabilize the fracture site. These limbs very frequently require multiple surgeries, which predisposes them to problems like heel pressure sore, equinus deformity and limb edema. These complications prolong the healing time and create obstacles in rehabilitation. Our aim was to modify the usual uniplanar external fixator in such a way that it is able to provide stable limb elevation and also keep the leg and the foot in such a position, so as to avoid the above-mentioned complications. We used our frame in 10 patients and none of our patients developed heel ulceration or equinus deformity. We found that the frame enables easier daily examination of the wound and improves patient comfort during dressing changes.
Keywords: equinus contracture; heel ulceration; limb elevation; modification of external fixator frame